The Evaluation of web-based and android face-to-face tutorial applications quality using the user acceptance testing (UAT) method - arif, Erman; Paulina Soko, Imelda (Journal of World Science, 2022)
Problems in the learning system at the Universitas Terbuka Basically no only focus against the tutorial in network only, but also on service help study stare advance that is not yet there is a system for monitor to what extent are the activities of the Tutorial Gaze Face (TTM). Studies this aim for measure how far is the quality Gaze Tutorial app Advance Web Based And Android.Methods used in measure quality application is use User Acceptance Testing (UAT) method. of several amount respondent could taken conclusion how far is the quality applications that have been done made in form prototype. After To do testing could taken conclusion that face tutorial app advance have attractive appearance, easy menus understood, content or Theory easy understood and understood, application this can also used as media in tutorial activities